Effect of 4-hydroxybenzoic acid on grape (Vitis vinifera L.) soil microbial community structure and functional diversity - Guo, Xiu-wu; Wang, Bo; Li, Kun; Liu, Zhen-dong; Han, Xiao; Xu, Shi-jie; Guo, Yin-shan; Xie, Hong-gang (Biotechnology, biotechnological equipment, 2015)
Phenolic compounds are considered to be an important autotoxic substances. The interactions between them and soil microbes are increasingly becoming a focus of the allelopathic research studies. In the present study, we have evaluated the effect of 4-hydroxybenzoic acid on soil microbial community structure and functional diversity. Bulk soil without grapevine cuttings (Group 1) and rhizosphere soil with Beta (Vitis riparia × Vitis labrusca) grapevine cuttings (Group 2) were used as research subjects. The bacterial (16s rRNA) and fungal internal transcribed spacer regions community structures were obtained using a denaturing gradient gel electrophoresis and substrate utilization patterns were determined using Biolog EcoPlates. In this research, the results showed that the 4-hydroxybenzoic acid caused a shift in the soil bacterial and fungal community structures and changed the soil microbial functional diversity. The results also showed that the diversity of the microbial community structure and function differed between the two designated groups. The application of 4-hydroxybenzoic acid (1 and 2 mg/g) to the soil resulted in a greater decrease in the average diversity of the bacterial community structure in Group 2, compared to Group 1. Moreover, the average diversity of the fungal community structure in Group 2 became higher than that in Group 1. However, the bacterial and fungal community structural diversities increased with the application of 0.5 mg/g of 4-hydroxybenzoic acid. Thus, we concluded that both soil microbes and root exudates might be the recipients of 4-hydroxybenzoic acid.